Machine tool vibrations and cutting dynamics - Gegg, Brandon C.; Suh,C. Steve; Luo,Albert C. J.; SpringerLink (Online service). (New York Springer, 2011)
Machine Tool Vibrations and Cutting Dynamics covers the fundamentals of cutting dynamics from the perspective of discontinuous systems theory. It shows the reader how to use coupling, interaction, and different cutting states to mitigate machining instability and enable better machine tool design. Among the topics discussed in this book are: underlying dynamics of cutting and interruptions in cutting motions; the operation of the machine-tool systems over a broad range of operating conditions with minimal vibration, and the need for high precision, high yield micro- and nano-machining. In addition, this volume also: Presents the underlying dynamics of cutting and interruptions in cutting motions Demonstrates the operation of the machine-tool systems over a broad range of operating conditions with minimal vibration such as high speed operation to achieve high quality finish of the machined surface Shows how to increase the rate of production to maximize profit and minimize operating and maintenance costs Machine Tool Vibrations and Cutting Dynamics is an ideal volume for researchers and engineers working in mechanical engineering and engineering systems.
Introduction: The Machining Problem -- Discontinuous System Theory -- Frictional-Induced Oscillators -- Cutting Dynamics Mechanisms -- Regular and Chaotic Motions in Cutting Processes -- Appendices.
Electronic reproduction.
Keywords: Electronic books; Machining -- Dynamics; Cutting -- Dynamics; Machinery, Dynamics of